AKSESIBILITAS DALAM PELAYANAN PUBLIK UNTUK MASYARAKAT DENGAN KEBUTUHAN KHUSUS - dan Fajar Iswahyudi, Ferry Firdaus (Jurnal Borneo Administrator, 2010)
State protection for citizens and society should be developed and facilitated without any discrimination. This also applies to public services which should be provided by the public sectors disregarding any limitations of the beneficiaries. This has become a big issue if it is related to what the Indonesian public sectors have facilitated so far. State laws, regulations and policies had been established with little compliance from the public sectors. The government themselves tended to ignore the situation, consequently the results of public services for the people with different abilities (difabel) had gone long unnoticed. This paper aimed at highlighting the needs of ensuring public services accessible to their beneficiaries disregarding their physical, mental, or language limitations and urging the needs of improving awareness as well as real actions for combating differences and discriminations and empowering the Difabel society with more access to public services. Providing more access for difabel society to public services would surely contribute to the improvement of state protection for its citizens and society.   Keywords: Accessibility, Difabel, Public Services